HUBUNGAN PENGETAHUAN TANDA-TANDA BAHAYA KEHAMILAN DAN PRAKTIK IBU HAMIL SAAT MENGALAMI KOMPLIKASI KEHAMILAN - Maryuni Maryuni; Mella Yuria Rachma Anandita; Legina Anggraeni (LPPM Universitas Abdurrab, 2021)
Pregnancy and childbirth are very important events for every woman and her family. But this event can be a complication for the mother and the baby she is carrying. Maternal death is generally influenced by two causal factors, namely direct cause and indirect cause. The direct cause of maternal death is a factor associated with complications of pregnancy, childbirth and childbirth. This research is an analytical research with cross sectional design. The number of samples used as many as 111 pregnant women scattered in jakarta and surrounding areas. The results of this study found the results of chi square test found the result of p value 0.091 which means there is no significant relationship. It is expected that with this research other research can increase the number of variables associated with the practices and behaviors of pregnant women when experiencing complications in their pregnancy.